2021
DOI: 10.1039/d1mh00733e
|View full text |Cite
|
Sign up to set email alerts
|

Super-ions of sodium cations with hydrated hydroxide anions: inorganic structure-directing agents in zeolite synthesis

Abstract: In inorganic zeolite formation, a direct correspondence between liquid state species in the synthesis and the supramolecular decoration of the pores in the as-made final zeolite has never been reported....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…In analogy, concentrated NaOH mixtures wherein hydroxysodalite crystallizes ( Figure 2 ), a clear correspondence exists between the coordination assemblies of sodium clusters in the synthesis liquid and within the sodalite cages after crystallization. 4 Therefore, it can be suggested that zeolite polymorphism is, similar to zeolite composition, a direct result of the chemical state of the synthesis liquid prior to nucleation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In analogy, concentrated NaOH mixtures wherein hydroxysodalite crystallizes ( Figure 2 ), a clear correspondence exists between the coordination assemblies of sodium clusters in the synthesis liquid and within the sodalite cages after crystallization. 4 Therefore, it can be suggested that zeolite polymorphism is, similar to zeolite composition, a direct result of the chemical state of the synthesis liquid prior to nucleation.…”
Section: Discussionmentioning
confidence: 99%
“… 4 This complexity explains why even small variations of composition and conditions may turn synthesis to vastly different products. 4 8 Besides the framework topology, zeolite properties are determined by their composition, 9 characterized for aluminosilicate zeolites by the Si/Al ratio and extra-framework species. Lechert and co-workers 10 13 were first to empirically establish quantitative correlations between zeolite aluminum content and alkalinity of the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…Such an arrangement is reminiscent of the dense polyhedral networks in concentrated sodium hydroxide liquids. 55 , 56 …”
Section: Discussionmentioning
confidence: 99%
“…The symmetry and full structural models, including Al as well as anion ordering, were determined using NMR crystallography. Combining X-ray diffraction with Rietveld refinement and advanced solid-state NMR in a NMR crystallography approach, [22] diffraction enables to selectively derive the structure and periodicity of the crystalline parts of a sample. NMR reveals local structural information on all phases present and exploits advanced experiments and filtering schemes, to highlight specific parts in the sample or selectively investigate well defined interactions between atoms.…”
Section: Introductionmentioning
confidence: 99%